Blockchain for Medical Records: Ensuring Security, Privacy, and Interoperability in Global Health - Ali Reza; Leila Mahdavi; Fatemeh Hashemi; Rustiyana Rustiyana (Journal of World Future Medicine, Health and Nursing, 2025)
Medical records play a critical role in healthcare delivery, yet existing digital health systems face persistent challenges related to data security, patient privacy, and interoperability across institutions and national borders. Blockchain technology has been proposed as a potential solution to these challenges, particularly within the context of global health systems characterized by fragmentation and regulatory diversity. This study aims to examine how blockchain technology is applied to medical record management in global health, with a focus on its capacity to ensure security, protect privacy, and support interoperability across healthcare systems. The study adopts a qualitative descriptive approach using systematic literature review and comparative case analysis. Secondary data are collected from peer-reviewed publications, policy reports, and documented blockchain-based medical record implementations across multiple regions. Data are analyzed through thematic synthesis and cross-case comparison. The findings reveal that blockchain adoption in medical records is unevenly distributed across regions and is strongly influenced by digital infrastructure readiness and regulatory environments. The study concludes that blockchain functions as an adaptive socio-technical infrastructure rather than a universal solution for medical records.